2014
DOI: 10.1002/2014gl061823
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ENSO on formation of tropical cloud clusters and their development into tropical cyclones in the western North Pacific

Abstract: This study analyzes the influence of El Niño-Southern Oscillation (ENSO) on the activity of tropical cloud clusters (TCCs) in the western North Pacific (WNP). A TCC must have at least one embedded mesoscale convective system and it must persist for more than 24 hours. In all, 2,248 TCCs were identified during July-October 1981-2009. While more (less) TCCs form in the eastern (western) part of the WNP during El Niño years than during normal years, the converse is true during La Niña years. The ratio of tropical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 23 publications
(61 reference statements)
3
27
1
Order By: Relevance
“…They have captured much attention due to their extensive impacts, including strong winds, precipitation, flooding, hail and lightning (Houze 2004). MCSs that occur over ocean regions can be precursors of tropical cyclones (Bister 1996;Gray 1998;Teng et al 2014). Moreover, they play a critical role in connecting atmospheric convection with large-scale atmospheric circulation patterns (Chen et al 1996;Laing and Fritsch 2000;Moncrieff 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They have captured much attention due to their extensive impacts, including strong winds, precipitation, flooding, hail and lightning (Houze 2004). MCSs that occur over ocean regions can be precursors of tropical cyclones (Bister 1996;Gray 1998;Teng et al 2014). Moreover, they play a critical role in connecting atmospheric convection with large-scale atmospheric circulation patterns (Chen et al 1996;Laing and Fritsch 2000;Moncrieff 2010).…”
Section: Introductionmentioning
confidence: 99%
“…4 except for the 850-hPa wind field (stream line) and the anomalies of relative vorticity (shaded, 10 -5 s -1 , which passes the t test at a 90% confidence level) from the climatology (1970 -2014). the TC activity in the entire WNP (Chan 2000;Teng et al 2014). Previous studies have verified that the TC activity in the entire WNP has the interdecadal variations, which are attributed to the decadal variations of large-scale sea surface temperature, low-level vorticity, and vertical wind shear in the WNP (Chan 2008;Chan 2008, 2013;Zhao and Wang 2016).…”
Section: Discussionmentioning
confidence: 90%
“…However, teleconnections can also be observed; there is an increase in occurrence over the Northwest United States (25–55°N, 100–120°W) and Indian Ocean (10°S–10°N, 40°–80°E) and a decrease in the Atlantic basin (10°S–10°N, 60°–10°W) during El Niño. Teng et al [] have shown that there are both increases in cloud cluster occurrence as well as their likelihood of forming tropical cyclones in the western North Pacific during El Niño.…”
Section: Resultsmentioning
confidence: 99%